Shear bond strength of metallic brackets bonded to enamel pretreated with CPP-ACP: a systematic review and meta-analysis of in vitro studies - Yomna M. Yacout; Yomna A. Nabawy; Nadia M. El-Harouni; Tarek N. Yousry (BMC, 2023)
Abstract Background Development of white spot lesions (WSLs) is common among orthodontic patients. Several measures have been introduced to prevent and remineralize the lesions. Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) is used for both prevention and remineralization. The effect of its application before bonding is controversial. This systematic review was conducted to investigate the most up to date available literature regarding the effect of CPP-ACP enamel pre-treatment on shear bond strength (SBS) of metallic orthodontic brackets. Methods A search was conducted in electronic databases (MEDLINE (via PubMed), Scopus, Cochrane Library, Web of Science and Google scholar (grey literature)) up to March 29th, 2023. The inclusion criteria included in vitro studies comparing the SBS of metal orthodontic brackets following pre-treatment of enamel using CPP-ACP versus control. The exclusion criteria included study types other than in vitro studies, studies conducted on non-human enamel, or studies using CPP-ACP in combination with another intervention. The included studies were analysed by two reviewers, independently. The risk of bias assessment was done using a modified risk of bias tool. A Meta-analysis was performed. I2 values and Q-test were used for assessment of heterogeneity. Results were displayed in forest plots with a random-effects model. Standardized mean difference, standard error (SE) and 95% confidence intervals were calculated for all studies. Results The search resulted in 76 articles. After duplicate removal and assessment for eligibility, 15 studies were included in the review. High statistical heterogeneity was found among the included studies using I2 values and Q-Test (I2 = 95.147%; Q = 288.456; df = 14; P < 0.001). The overall effect of CPP-ACP pre-treatment on the SBS of metal orthodontic brackets was not significant (Mean difference = 1.163 MPa, SE = 0.757, 95% CI = -0.321, 2.648, p value = 0.125). The use of CPP-ACP for prevention of WSLs did not significantly affect the SBS of brackets (Standardized mean difference = 1.009, SE = 0.884, 95% CI = -0.723, 2.740, p value = 0.254). No significant change was found when CPP-ACP was used for remineralization of WSLs (Standardized mean difference = 1.501, SE = 1.087, 95% CI = -0.630, 3.632, p value = 0.167). Conclusions Within the limitations of the study, the evidence suggests that the use of CPP-ACP for either prevention or remineralization of WSLs before bonding does not affect the SBS of metal orthodontic brackets.